Overexpression of CaWRKY27, a subgroup IIe WRKY transcription factor of Capsicum annuum, positively regulates tobacco resistance to Ralstonia solanacearum infection. Issue 3 (16th October 2013) - Dang, Fengfeng; Wang, Yuna; She, Jianju; Lei, Yufen; Liu, Zhiqin; Eulgem, Thomas; Lai, Yan; Lin, Jing; Yu, Lu; Lei, Dan; Guan, Deyi; Li, Xia; et al.
<x xml:space="preserve">Abstract</x> WRKY proteins are encoded by a large gene family and are linked to many biological processes across a range of plant species. The functions and underlying mechanisms of WRKY proteins have been investigated primarily in model plants such as Arabidopsis and rice. The roles of these transcription factors in non‐model plants, including pepper and other Solanaceae, are poorly understood. Here, we characterize the expression and function of a subgroup IIe WRKY protein from pepper (Capsicum annuum), denoted as CaWRKY27. The protein localized to nuclei and activated the transcription of a reporter GUS gene construct driven by the 35S promoter that contained two copies of the W‐box in its proximal upstream region. Inoculation of pepper cultivars with Ralstonia solanacearum induced the expression of CaWRKY27 transcript in 76a, a bacterial wilt‐resistant pepper cultivar, whereas it downregulated the expression of CaWRKY27 transcript in Gui‐1‐3, a bacterial wilt‐susceptible pepper cultivar. CaWRKY27 transcript levels were also increased by treatments with salicylic acid (SA), methyl jasmonate (MeJA) and ethephon (ETH). Transgenic tobacco plants overexpressing CaWRKY27 exhibited resistance to R. solanacearum infection compared to that of wild‐type plants. This resistance was coupled with increased transcript levels in a number of marker genes, including hypersensitive response genes, and SA‐, JA‐ and ET‐associated genes. By contrast, virus‐induced gene silencing (VIGS) of CaWRKY27 increased the susceptibility of pepper plants to R. solanacearum infection. These results suggest that CaWRKY27 acts as a positive regulator in tobacco resistance responses to R. solanacearum infection through modulation of SA‐, JA‐ and ET‐mediated signaling pathways.